Pelatihan Pembuatan Buket Klobot dan Strategi Digital Marketing untuk Meningkatkan Ekonomi Kreatif Ibu-Ibu PKK Desa Kalinanas - Melly Eka Kharisma; Ahmad Setya Fany; Nihayatur Rifah; Alfito Ari Praditya; Wakhid Fitri Albar (Jurnal Dharma Indonesia, 2026)
Kalinanas Village, Japah District, has abundant corn-growing potential. However, corn husks, locally known as klobot, are still considered waste. In fact, corn husks can be processed into value-added products such as bouquets. On the other hand, PKK women, as key drivers of the village economy, still have limitations in utilizing digital marketing strategies. Therefore, the UNNES GIAT 12 Community Service Program (KKN) team conducted training on making corn husk bouquets and digital marketing using participatory methods, including socialization, hands-on practice, and mentoring. The activity was attended by 25 participants, divided into three groups, each producing two corn-husk bouquets, resulting in a total of six bouquets as final products. Participants were involved in all stages of production, from material processing to bouquet assembly, and were also introduced to the use of social media as a marketing tool. The results indicate that this activity encouraged community participation in utilizing corn husk waste into creative products and created opportunities for small-scale home-based businesses.